2014
DOI: 10.1007/s11031-014-9422-5
|View full text |Cite
|
Sign up to set email alerts
|

Student engagement and performance: A weekly diary study on the role of openness

Abstract: In the present study, we used a quantitative diary design to investigate within-person fluctuations in student engagement and performance. Specifically, we analyzed the impact of weekly personal and study resources on weekly student engagement, active learning behaviors, and performance. In addition, we investigated whether students high (vs. low) in trait Openness reacted differently to their weekly resources. The sample was composed of 45 first-year psychology students who filled in a questionnaire over 3 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
131
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(148 citation statements)
references
References 54 publications
11
131
0
6
Order By: Relevance
“…Open wasn't discussed in relation to the nature of student relationships and classroom discussions (Alivernini & Manganelli, 2011) (Bakker et al, 2015), so not reflecting the humanistic approaches developing in primary schools in the 1970's (Katz, 1972). Open practice described in the present study did not reflect the broader scholarly activities observed by Veletsianos and Kimmons (2012), such as open access publishing of journal articles and data, or maintaining a blog and/or social media presence.…”
Section: What Openness Wasn't?mentioning
confidence: 99%
See 1 more Smart Citation
“…Open wasn't discussed in relation to the nature of student relationships and classroom discussions (Alivernini & Manganelli, 2011) (Bakker et al, 2015), so not reflecting the humanistic approaches developing in primary schools in the 1970's (Katz, 1972). Open practice described in the present study did not reflect the broader scholarly activities observed by Veletsianos and Kimmons (2012), such as open access publishing of journal articles and data, or maintaining a blog and/or social media presence.…”
Section: What Openness Wasn't?mentioning
confidence: 99%
“…Schools strive to foster a culture of openness in classrooms when debating social and political issues to encourage independent thought (Alivernini & Manganelli, 2011). In one study of psychology students, openness and "openness to experience" was identified as a personality trait linked to higher levels of engagement with learning (Bakker, Vergel, & Kuntze, 2015). At institution level, it is being expressed as a strategic value representing the important position of higher education in society (Wiley & Hilton, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, effective interventions should attend to this important variable, focusing on its antecedents to help its development. In this sense, efforts from teachers and family (which are social facilitators as well) may help students to improve their engagement (Bakker et al 2015). For example, it is possible to reduce student's fear of failure through positive reinforcement and frequent feedback (Caraway et al 2003), which also influence positive emotions that are relevant for academic engagement (Reschly et al 2008).…”
Section: Implications For Practicementioning
confidence: 99%
“…Galbraith and Fouch (2007) emphasized the importance of focusing on adult learning strategies and understanding the role of andragogy in adult best illustrates the overall focus on andragogy (Galbraith & Fouch, 2007). Baker, Sanz Vergel, and Kuntze (2015) found that student engagement in the classroom is malleable. Adult participants in any course will need to understand the small and larger picture and invest time and effort in each student success rate as well as student engagement (Baker et al, 2015).…”
Section: Activities Through Which We Learnmentioning
confidence: 99%
“…Baker, Sanz Vergel, and Kuntze (2015) found that student engagement in the classroom is malleable. Adult participants in any course will need to understand the small and larger picture and invest time and effort in each student success rate as well as student engagement (Baker et al, 2015).…”
Section: Activities Through Which We Learnmentioning
confidence: 99%